English Vocabulary in Use. Advansed - McCarthy M. Michael (New York, Cambridge University Press, 2007)
English Vocabulary in Use Advanced is a vocabulary book for advanced level learners. It is primarily designed as a self-study reference and practice text but it can also be used for classroom work. English Vocabulary in Use Advanced• 100 easy-to-use two-page units: vocabulary items are presented and explained on left-hand pages with a range of practice exercises on right-hand pages. Presents and explains new words in context and shows learners how to use them. Uses short texts and typical example sentences to ensure students are exposed to real language. Based on a corpus of written and spoken language to ensure the vocabulary is relevant and up-to-date.